COMPARISON OF A RADIATION DOSE DURING STANDARD DIGITAL RADIOGRAPHY, TOMOSYNTHESIS, AND MULTISLICE SPIRAL COMPUTED TOMOGRAPHY IN AN EXPERIMENTAL STUDY OF PEDIATRIC ANTHROPOMORPHIC PHANTOM - A. Yu. Vasil’ev; S. S. Karpov (Вестник рентгенологии и радиологии)
Objective: to compare a radiation dose obtained during standard digital radiography, tomosynthesis, and multislice spiral computed tomography (MSCT). Material and methods. Life-size full body pediatric anthropomorphic mannequin phantom was examined with a Fujifilm FDR Ac Selerate 200 X-ray diagnostic apparatus and a Toshiba Aquilion Prime 64 computed scanner using the Piranha dosimetry equipment, as well as Gammex planar target, for comparison of the resolution of the apparatus. The effective radiation doses were calculated for different anatomical regions with the formulas specified in the methodical instructions, using the coefficients K and Kd. Results. The tables and graphs comparing the radiation dose when using different radiation diagnostic techniques were presented. The resolution of standard digital radiography versus that of tomosynthesis was analyzed. Fluctuations of the doses obtained were associated with the difference in the volume of irradiated tissue and in the presence of the doses in the irradiated volume of organs with high radiosensitivity. Optimal physical and technical parameters of photography were proposed, which could reduce a dose load on the patient, without significantly losing the quality of films. Conclusion. The effective doses of tomosynthesis were significantly higher than those of standard digital radiography (p < 0.05) while those of (MSCT) were above those of both X-ray and tomosynthesis, and the resolution of the latter was slightly lower.